2002
DOI: 10.1302/0301-620x.84b5.0840658
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, controlled trial of cemented versus cementless press-fit condylar total knee replacement

Abstract: We have carried out a long-term survival analysis of a prospective, randomised trial comparing cemented with cementless fixation of press-fit condylar primary total knee replacements. A consecutive series of 501 replacements received either cemented (219 patients, 277 implants) or cementless (177 patients, 224 implants) fixation.The patients were contacted at a mean follow-up of 7.4 years (2.7 to 13.0) to establish the rate of survival of the implant. The ten-year survival was compared using life-table and Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 20 publications
0
48
2
3
Order By: Relevance
“…Cement versus cementless fixation for TKA continues to be a topic of debate and has received much attention in the literature [2,4,6,13]. However, little data exists concerning the issue of cement or cementless keel/stem fixation in association with cemented tibial tray fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Cement versus cementless fixation for TKA continues to be a topic of debate and has received much attention in the literature [2,4,6,13]. However, little data exists concerning the issue of cement or cementless keel/stem fixation in association with cemented tibial tray fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is now clear that aseptic loosening is mainly related to debris from polyethylene wear rather than failure of cemented fixation [12][13][14][15], the question remains whether cementless TKAs have an improved long-term survival. This can only be answered by a randomised trial comparing the two methods of fixation.…”
Section: Introductionmentioning
confidence: 99%
“…However, with time, problems with cementless implants have been overcome by better designs and new fixation systems, reducing the risk of early migration [62] and loosening of the tibial component [18], and resulting in clinical results and survivorship rates comparable to those achieved with cemented implants [5,7,8,18,19,24,25,33,40,46,51,65,66]. However, given the similarity of results, some of these authors have concluded that the lack of advantages of uncemented over cemented components would not support the use of more expensive implants [19,33].…”
Section: Introductionmentioning
confidence: 99%